The EU accession to the ECHR: an attempt to explore possible implications in the area of public procurement - Georgopoulos, Aris (Hart Publishing, 2014)
The aim of this paper is two fold. First, it tries to map out the areas of potential interplay/interaction between public procurement and human rights. Second, it explores whether the prospective accession of the EU to the ECHR will have concrete consequences in the area of public procurement regulation and practice by creating new pathways/areas of intersections/interaction and/or strengthen existing ones, thus rendering them more attractive. Finally, it will argue that the EU’s accession might have a qualitative impact by assisting the shift in the balance between market freedoms and human rights that began with the coming into force of the Treaty of Lisbon and the European Charter of Fundamental Rights.